A prison audience: women prisoners, Shakespeare and spectatorship. Issue 2 (27th May 2019) - Reason, Matthew
ABSTRACT: In 2017 the Donmar Warehouse presented The Tempest to women prisoners at HMP New Hall, UK. The production was part of a trilogy of Shakespeare plays directed by Phyllida Lloyd, each staged with an all-female cast and each set within a women's prison. Over the five years of developing this trilogy the Donmar undertook extensive research and development into the prison context, including in collaboration with York St John University's Prison Partnership Project. This paper explores the prison audiences' experiences of The Tempest, examining how they responded to seeing their own lived experiences on stage, filtered through the prism of Shakespearian plot, characterisation and language. In particular, this paper focuses on moments of identification, where the women found direct resonance and self-recognition with the characters and experiences in The Tempest . At the same time it draws on discourses from dramatherapy and aesthetic theory to argue for the importance of various forms of emotional, empathetic and psychical distance . Using close analysis of the spectators' responses, it describes how for the prison audience the result was an oscillation between identification and distance, a reading of "me but more than me" that produced a powerful affective and reflective impact.